Strategies for Transforming Waste into Creative Business Opportunities from a Circular Economy Perspective in Indonesia - Risky Shalsabila; Alexandra Venisia Kolo; Monika Evrista Mao Wao; Rosa Virginia Irimida Manek; Enike Tje Yustin Dima (Yayasan Pendidikan Islam Al-Matani, 2026)
The shift from a linear to a circular economic model demands innovation in waste management. This article analyzes the potential of waste as raw material for creative industries in Indonesia. By using a descriptive qualitative approach based on a literature review of various research journals, it was found that the integration of circular economy principles through product innovation, resource efficiency, and strengthening community institutions such as the Waste Bank was able to create significant added economic value. The analysis results show that the recycling and product innovation variables contribute 98.3% to the successful implementation of a circular economy. This article recommends strengthening Extended Producer Responsibility (EPR) regulations and market education